PEMANFAATAN UMBI KELADI DAN TEMPE DALAM PEMBUATAN NASI JINGGO - IRA HUBNER; ALICIA ANDERA; FIORENTINE GABRIEL (JURNAL ILMIAH SIMANTEK, 2021)
Nasi Jinggo is a typical Balinese food consisting of rice with its side dishes, namely satay lilit, cakes, shredded chicken,serundeng and sambal which are packaged using banana leaves. This study will utilize taro tubers and tempeh as asubstitute for chicken or meat in the making of Nasi Jingo side dishes, because taro tubers and tempeh have elements ofgood health, are easy to obtain and from a price point of view are also quite affordable. The purpose of this study was todetermine the quality or quality as well as the level of preference of jinggo rice with taro tubers and tempeh as raw materials.This product research method will use the organoleptic test, both the hedonic quality test to determine quality and thehedonic test to assess the level of preference. Determination of sample of expert panelists at the initial stage of productdesign and testing using purposive sampling (expert criteria). Determination of the sample of panelists from potential user /consumer groups at the end of the product using convenience or quota sampling. Data from filling out the questionnaire bypanelists will be processed using SPSS. The results showed that the value of the quality and the value of the community(panelists) 's favorite value of jinggo rice with taro and tempeh as raw material was declared very good for quality and veryfond of liking.